The associations of SES, obesity, sport activity, and perceived neighborhood environments: Is there a model of environmental injustice penalizing portuguese children?. Issue 3 (4th April 2013) - Nogueira, Helena; Gama, Augusta; Mourão, Isabel; Marques, Vitor; Ferrão, Maria; Padez, Cristina
<x xml:space="preserve">Abstract</x> Objectives This study analyses the associations between children's obesity, sports activity (SA), and perceived environmental characteristics with the children's SES. Methods A sample of 1, 885 Portuguese children, aged 3–10 years, living in Coimbra, Portugal, was observed. Weight and height were measured and obesity was defined by age‐and sex‐specific, BMI cut‐off points. Questionnaires included variables on SA levels, SES and parental neighborhood perceptions were done. A CATPCA was performed and two neighborhood dimensions were achieved. The independent associations of SES with obesity, SA and perceived neighborhood dimensions was analyzed using ordered logistic regressions. Results Children of low [odds ratio (OR) = 1.76; confidence interval (CI) = 1.25–1.99] and medium SES (OR = 1.57; CI = 1.34–2.33) were more likely to be obese than their high‐SES peers, less likely to participate in SA (low SES OR = 0.177; CI = 0.12–0.26; medium SES OR = 0.357; CI = 0.24–0.53), and their parents were less likely to have positive perceptions of their built environment (low SES OR = 0.516; CI = 0.38–0.70; medium SES OR = 0.565; CI = 0.37–0.86). Conclusions Obesity increases and SA decreases among children with the lowest SES and these living in neighborhoods with higher perceived risk. This finding suggests a model of environmental injustice, whereby differential access to the neighborhood's resources overlaps with familial socioeconomic disadvantage. Am. J. Hum. Biol. 25:434–436, 2013. © 2013 Wiley Periodicals, Inc.